Taxonomic review of Rhyacobates Esaki, 1923, with descriptions of three new species (Hemiptera: Heteroptera: Gerridae) - Leng, Zhaoqi; Tran, Anh Duc; Ye, Zhen (European Journal of Taxonomy, 2023)
The species of Rhyacobates Esaki, 1923 are reviewed. Three new species, R. bui sp. nov. from Guangxi, China and Lạng Sơn, Vietnam, R. elongatus sp. nov. from Hà Tĩnh, Vietnam and R. turgidus sp. nov. from Sichuan and Chongqing, China are described. Supplemental descriptions, diagnoses and new distribution records are provided for the fourteen previously known species, i.e., R. abdominalis Andersen & Chen, 1995, R. anderseni Tran & Yang, 2006, R. angustus Tran & Nguyen, 2016, R. chinensis Hungerford & Matsuda, 1959, R. constrictus Tran & Nguyen, 2016, R. edentatus Andersen & Chen, 1995, R. gongvo Tran & Yang, 2006, R. lundbladi (Hungerford, 1957), R. malaisei Andersen & Chen, 1995, R. recurvus Andersen & Chen, 1995, R. scorpio Andersen & Chen, 1995, R. svenhedini (Lundblad, 1934), R. takahashii Esaki, 1923, and R. zetteli Tran & Nguyen, 2016. Photographs and line drawings of the habitus, diagnostic characteristics of both sexes, the habitat and in-situ photographs are presented. A revised key to the species of Rhyacobates is also provided.